Rapid depletion of B lymphocytes by ultra-low-dose rituximab delivered intrathecally. Issue 2 (April 2015) - Svenningsson, Anders; Bergman, Joakim; Dring, Ann; Vågberg, Mattias; Birgander, Richard; Lindqvist, Thomas; Gilthorpe, Jonathan; Bergenheim, Tommy
Abstract : Objective: We are conducting an open-label phase 1b study on the efficacy of intrathecal (IT) administration of rituximab, provided via an Ommaya reservoir, for the treatment of progressive multiple sclerosis (PMS). The objective of this initial study was to monitor B lymphocytes in peripheral blood (PB) and CSF from the first 10 patients 1 year posttreatment. Methods: Dose titration was performed with daily escalation from 1 mg to 25 mg IT rituximab (n = 3). Lymphocyte subpopulations were monitored daily during dose escalation in PB by flow cytometry and subsequently every 3 months for 1 year, after a total dose of 3 × 25 mg. PB B-lymphocyte subpopulations for the remaining patients (n = 7) were monitored at regular intervals. CSF lymphocyte subpopulations for all patients were monitored by flow cytometry every 2–3 months. Results: The PB B-lymphocyte count dropped rapidly after the first 2 injections (total dose of 3.5 mg IT rituximab) to undetectable levels. Three 25-mg doses given once per week depleted peripheral B lymphocytes entirely for the following 3–6 month period. Conclusions: Monoclonal antibodies seem to rapidly redistribute to the peripheral compartment following IT injection. Ultra-low doses of rituximab given IT are sufficient to cause complete depletion of peripheral B lymphocytes, indicating that low-dose IT treatment has the potential to be effective in both the CNS and systemic compartments. Classification of evidence: This study provides Class IV evidence that for patients with PMS, rituximab provided via an Ommaya reservoir depletes peripheral blood B lymphocytes.